Wash‐free, peptide‐based fluorogenic probes for microbial imaging. Issue 1 (7th May 2020) - Baibek, Assel; Üçüncü, Muhammed; Blackburn, Elizabeth A.; Bradley, Mark; Lilienkampf, Annamaria
Abstract: Peptides with pan‐antimicrobial affinity were synthesized and decorated with environmentally sensitive fluorophores nitrobenzoxadiazole (green) and merocyanine (red). The labeling efficacies against a range of clinically relevant fungal and Gram‐negative and positive bacterial species ( Candida albicans, Escherichia coli, and Staphylococcus aureus ) were explored. The fluorogenic probes containing exclusively l or d ‐amino acids showed rapid and efficient labeling of all microbial species, whereas probes with a mixture of l or d ‐amino acids failed to label fungi or bacteria, highlighting the importance of the α‐helical peptide structure for interaction with the microbial cell membrane. Importantly, the nature of the dye allowed fluorescence detection/labeling without the need for a wash step, paving the way for direct application of the probes. Abstract :